IMPULSE RESPONSE OF THE KINEMATIC DIFFUSION MODEL AS A PROBABILITY DISTRIBUTION OF HYDROLOGIC SAMPLES WITH ZERO VALUES - Strupczewski W.G.; Weglarczyk S.; Singh V.P. (My University, 2003)
It is hypothesized that the unit impulse response of a linearized kinematic diffusion (KD) model is a probability distribution suitable for frequency analysis of hydrologic samples with zero values. Such samples may include data on monthly precipitation in dry seasons, annual low flow, and annual maximum peak discharge observed in arid and semiarid regions. The hypothesized probability distribution has two parameters, which are estimated using the methods of moments (MOM) and maximum likelihood (MLM). Also estimated are errors in quantiles for MOM and MLM. The distribution shows an equivalency of MOM and MLM with respect to the mean value-an important property for ML-estimation in the case of the unknown true distribution function. The hypothesized KD distribution is tested on 44 discharge data series and compared with the Muskingum-like (M-like) probability distribution function. A comparison of empirical distribution with KD and M-like distributions shows that MOM better reproduces the upper tail of the distribution, while MLM is more robust for higher sample values and more conditioned on the value of the probability of the zero value event. The KD-model is suitable for frequency analysis of short samples with zero values and it is more universal than the M-like model as its modal value cannot be only equaled to zero value but also to any positive value.
Keywords: PROBABILITY DISTRIBUTION; EPHEMERAL STREAMS; FREQUENCY ANALYSIS; HYDROLOGIC EXTREMES; KINEMATIC DIFFUSION; PARAMETER ESTIMATION; TIME SERIES